KERAGAMAN SIFAT KUALITATIF AYAM KAMPUNG DI MINAHASA - Kolompoy, Monika; Lambey, Lucia J.; Paputungan, Umar; Tangkere, E.S. (Universitas Sam Ratulangi, 2020)
THE DIVERSITY OF QUALITATIVE CHARACTERISTICS IN NATIVE CHICKEN AROUND MINAHASA. This study aims to determine the diversity of qualitative characteristics in native chicken around Minahasa Regency. A total of 292 adult chickens were used as samples taken randomly and analyzed using descriptive methods. The results showed that the phenotype frequency, color genotype and feather pattern were 0.000515. Trait frequencies of comb shape was 0.000458, cupping color was 0.9957, foot skin color was 0.9949, and spur shape was 0.000193. The degree of heterosigosity of qualitative characteristics of Kampung chickens in Minahasa on average was in the medium category (0.20) to high (0.50). The degree of heterosigosity of the phenotypic traits of native chicken in Minahasa indicated the relative low degree of inbreeding mating. Distribution of phenotypic inheritance of feather color, comb shape and shape of male foot spurs based on samples of native chicken populations were not in genetic equilibrium. The qualitative traits of native chickens in the Minahasa Regency showed a fairly high level of diversity. Key words: native chicken, qualitative characteristics.